Estimation of genetic parameters for litter size in pigs from different genetic groups - Logar, Betka; Kovač, Milena; Malovrh, Špela Pezdevšek (Acta Agraria Kaposváriensis, 1999)
Number of piglets born alive (NBA) and number of piglets born (NB) was analysed. A total of 46,960 litters of Swedish Landrace (SL) Large White (LW), and both F1 sows were included. Records were collected between 1993 and 1998. Animal model and REML procedures were used to estimate genetic and environmental parameters for the first sixth litters in univariate analyses. Random additive genetic effect and permanent environment effect of the sow were considered. The differences between genotypes were estimated by crossbreeding parameters: additive maternal and additive grand-maternal effect as well as maternal heterosis. Estimates were 0.14 and 0.12 for heritability and 0.20 and 0.18 for repeatability in NB and NBA respectively. The contribution of additive maternal effect to the breed differences (SL-LW) was estimated at 0.10 and 0.26 respectively. The estimated deviation of the F1 from the mid parental value (maternal heterosis effect) was 0.69 and 0.72 for NB and NBA respectively. The additive grand- maternal effect, which expresses the differences between crossbreeds, (SL x LW-LW x SL) was low (0.06 for NB and -0.03 for NBA).
Keywords: pigs; litter size; variance components; heritability; crossbreeding parameters